Car accident prevention by using tilt sensor / Muhammad Izzat Roslan, Wan Ahmad Firdaus Wan Azhar and Mohamad Arif Syafiq Mohamad Rohim - Roslan, Muhammad Izzat; Wan Azhar, Wan Ahmad Firdaus; Mohamad Rohim, Mohamad Arif Syafiq (2015)
This project is about car accident prevention by using tilt sensor based on the theme given which is health and safety. This project consists of one input which is the tilt sensor and consists of four outputs which are the vibrator, LED , LCD and the buzzer. This projects working principle is that when the input is high, all the outputs will trigger. Since the input is the tilt sensor, the variable that will be monitor or that will affect the sensor is movement. The tilt sensor will be place at spectacles. The sensor detects the movement of the driver’s head. The outputs are programmed to turn on when the head of the driver bends down for 3 seconds. If the 3 seconds is up, the LED will light, the buzzer will give out sound, vibrator will vibrate and the LCD will display “WAKE UP!” when initially displays “DRIVE SAVE”. The vibrator is placed at the neck of the driver or at the back of the driver. The placement of the LCD and buzzer is inside of a box created so that the prototype will look less messy and more organize. If the driver is awake and straighten his/her head again, the alarm will turn off and will turn back on again if the same scenario happens. That’s how the project works.